PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN RUMAH MAKAN LOMBOK HIJAU LAMONGAN - SETIA KUSUMA PUTRI, MERRY (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Business Developing this culinary often associated with high mobility community that more than. This is often associated with the workers or someone who is busy activities outside the house. One of them is by looking for food and drinks outside the house. To win the competition that more competitive business players are required to be able to create advantages to compete in the product and service in the effort satisfying consumers. The purpose of this study is to determine (1) The effect of service quality dimension consisting of tangibles, reliability, assurance, empathy and responsiveness, together (simultaneously) to consumer satisfaction of Restaurant Lombok Hijau Lamongan, (2) service quality dimension consisting of tangibles, reliability, assurance, empathy and responsiveness to weigh one by one to consumer satisfaction of Restaurant Lombok Hijau Lamongan, with variable dependent is customer satisfaction (Y), and variable independent are tangibles (X1), reliability (X2), assurance (X3), empathy (X4), and responsiveess (X5). This research aims to analyze and discuss the influence quality of service to customer satisfaction of Restaurant Lombok Hijau Lamongan. Types of research that is quantitative. Loading technique samples used by using Non-Probability Sampling. Taking sampel have to be delivered using methods without Forcible Entry sampling, with the number of sample as many as 205 respondents, and use multiple regression analysis tool in linear doubled to rescue fund software SPSS 16.0 for windows Results of the study showed that adjusted R square value of 49,5 % and most dominant variable is the variable reliability with standardized coefficient 34,6 %. The Keyword : Service Quality, Customer Satisfaction